ITS1 PCR-RFLP Diagnosis and Characterization of Leishmania in Clinical Samples and Strains from Cases of Human Cutaneous Leishmaniasis in States of the Mexican Southeast. (1st July 2014) - Monroy-Ostria, Amalia; Nasereddin, Abedelmajeed; Monteon, Victor M.; Guzmán-Bracho, Carmen; Jaffe, Charles L.
Abstract : American cutaneous leishmaniasis includes a spectrum of clinical forms localized cutaneous, diffuse cutaneous, and mucocutaneous leishmaniasis which can be caused by different strains of Leishmania belonging to the L. mexicana or L. braziliensis complexes which may coexist in the same endemic area. We evaluated the PCR-RFLP assay of the ITS1 genes for direct identification of Leishmania species in 163 clinical samples and 21 Mexican isolates of Leishmania . In relation to the Mexican isolates of Leishmania 52% displayed a pattern similar to the L. (L.) mexicana, 5% showed a mixed pattern compatible with L. (L.) mexicana and L. (V.) braziliensis, eight with L. (L.) amazonensis and L. (L.) mexicana, and one to L. (V.) braziliensis . Most of the clinical samples, 109/116 (94%), gave a pattern similar to that of the L. mexicana, two clinical samples gave similar patterns to that of Leishmania braziliensis, and 5 samples gave patterns that suggest a coinfection of L. (L.) mexicana and L. (V.) braziliensis or L. (L.) mexicana and L. (L.) amazonensis . The ITS1 PCR-RFLP assay is a multipurpose tool for diagnosis of Leishmania from clinical samples and enables determination of the infecting species of New World Leishmania in the field in relatively short time and low cost.